Analisis Dampak Covid-19 Terhadap Kinerja Keuangan Desa - Putri, Mira Novianti; Hendri, Nedi; Rahayu, Sri Retnaning (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to analyze the impact of COVID-19 on the financial performance of the village of Terbanggi Subing, Gunung Sugih District, Central Lampung Regency. This type of research is descriptive research with a qualitative approach. The data analysis technique used is using a qualitative descriptive analysis tool that is describing the data that has been obtained from the data collection technique used. The results of the study show that the financial performance of the village in Terbanggi Subing Village, Gunung Sugih District, Central Lampung, if calculated using the effectiveness ratio before the Covid-19 pandemic in 2018 was less effective, in 2019 it was effective, when the Covid-19 pandemic took place in 2020 it was already effective and in 2021 effective. Village financial performance is calculated using the efficiency ratio before the Covid-19 pandemic in 2018 was categorized as inefficient, in 2019 it was categorized as inefficient, and in 2020 when the Covid-19 pandemic took place it was categorized as inefficient, and in 2021 it was categorized as inefficient. Village financial performance if calculated using a growth ratio in 2019 before the covid-19 pandemic had grown positively, and in 2020 when the covid-19 pandemic was taking place it had grown positively, and in 2021 it was categorized as negative growth